STUDI TENTANG SIFAT FISIS KAYU LAPIS BERMUKA POLIURETAN - Achmad Supriadi; M. I. Iskandar (JURNAL SAINS NATURAL, 2014)
Study on Physical Properties of Polyurethane-faced Plywood        Polyurethane plywood include one of the products of secondary plywood that does not use adhesive coating. Giving a polyurethane coating can be a surface or both surfaces intended that plywood is more beautiful and more durable. The study aimed to examine the physical properties of the polyurethane-faced plywood from three companies. The results showed an average quality appearance included in A level. dimension covered an average thickness of 3.0 mm, a length of 2,440 mm, a width of 1220.2 mm and 2727.5 mm in diagonal, the water content of 10.25% and delamination of 10 mm. All the plywood of faced polyurethane material had resistance to acids, bases and diluent. All parameters of the physical properties of the polyurethane-faced plywood met the standards of buyers from Japan. Statistically there was no significant effect on the physical properties of the original material plywood of faced polyurethane. Polyurethane coated adhesive ability of polywood as the result of this research explained why the adhesive had been used extensively in composite wood products such as plywood.Keywords: Plywood polyurethane, quality appearance, physical properties, standard ABSTRAK         Kayu lapis bermuka poliuretan termasuk salah satu produk dari kayu lapis sekunder yang tidak menggunakan pelaburan perekat. Pemberian lapisan poliuretan bisa satu permukaan atau kedua permukaannya bertujuan agar kayu lapis lebih indah dan lebih tahan lama. Studi ini bertujuan untuk mencermati sifat fisis kayu lapis bermuka poliuretan yang berasal dari tiga perusahaan penghasil kayu lapis bermuka poliuretan. Hasil penelitian menunjukkan rata-rata mutu penampilan termasuk A. dimensi meliputi rata-rata tebal 3,0 mm, panjang 2.440 mm, lebar 1.220,2 mm dan diagonal 2.727,5 mm. Kadar air 10,25% dan delaminasi 10 mm. Semua bahan kayu lapis bermuka poliuretan memiliki ketahanan terhadap asam, basa dan pengencer. Semua parameter sifat fisis kayu lapis bermuka poliuretan memenuhi standar pembeli dari Jepang. Secara statistik tidak ada pengaruh nyata asal bahan terhadap sifat fisis kayu lapis bermuka poliuretan. Kemampuan perekat poliuretan untuk pelapis sebagaimana ditunjukkan dari hasil pencermatan ini ikut menjelaskan mengapa perekat ini telah digunakan luas pada produk komposit kayu termasuk kayu lapis.Kata kunci : Kayu lapis bermuka poliuretan, mutu penampilan, sifat fisis, standar